Efektivitas Komik Saku sebagai Media Pemilih dan Pemilu bagi Perempuan Marginal - Retno Widyastuti, Dhyah Ayu; Prasela, Mustika Kuri (Jurnal Ilmu Komunikasi, 2010)
Abstract: Womenâs participation in politics is very low particularly because of the situation in which women are marginalized both in terms of voters and candidates. In this sense, voter education based on gender perspective is one of the significance ways to increase womenâs political awareness. Pocket comic is seen as a media that can be used to achieve such awareness. This study examines the effectiveness of comic as an aid used in voter education in order to increase political participation of women as evaluators. This study found that pocket comic could be well understood by married women who received information from the media. Those women had also been trained by the Government and the PKK in the elections training through which they were stimulated to have gender awareness and then internalize it in their life.